Penggunaan Ventilasi Mekanik non Invansif Untuk Mengatasi Kegagalan Pernafasan pada Pasien dengan Edema Pulmo Akut Kardiogenik - Eva Marti (STIKes Panti Rapih, 2020)
Background: Cardiogenic Pulmo edema can cause a heterogeneous syndrome with a mortality rate of up to 9.5% (Aliberti et all., 2018).Objective: The purpose of this paper was to explain how effective the use of non-invasive mechanical ventilation in patients with acute pulmonary edema with respiratory failure. Methods: The literature review was compiled by synthesizing and comparing various relevant scientific articles from the literature search results using the online database of Proquest and Clinicalkey Elsevier that have significance related to the management of acute cardiogenic pulmo edema. Result: Compared with conservative therapy, noninvasive mechanical ventilation has been shown more effective in improving oxygenation in patients with acute cardiogenic pulmo edema Non-invasive ventilation can reduce dyspnea, acidosis and hypercapnea faster than standard oxygen therapy. Studies show that compared to endotracheal intubation, non-invasive mechanical ventilation is associated with a lower risk of nosocomial infection, lower antibiotic use, shorter length of stay in intensive care units and lower mortality. Study found that there were no differences betwen the two setting of non-invasive mechanical ventilation used, Bilevel positive Airway Pressure (BiPAP) and Continues positive Airway Pressure (CPAP) in patients outcomes. However, there are absolute and relative contraindications that must be considered, including the effectiveness of the therapy being insignificant when given too late Conclusion: Noninvasive mechanical ventilation can be considered as the first choice in the management of acute cardiogenic pulmonary edema because of its high clinical effectiveness representing a rescue action for patients not improving with conventional oxygen therapy.